Molecular identification and antimicrobial resistance pattern of seven clincal isolates of Nocardia spp. in Brazil - Condas, Larissa Anuska Zeni [UNESP]; Ribeiro, Marcio Garcia [UNESP]; Muro, Marisol Domingues; Vargas, Agueda Castagna de; Matsuzawa, Tetsuhiro; Yazawa, Katsukiyo; Siqueira, Amanda Keller [UNESP]; Salerno, Tatiana [UNESP]; Lara, Gustavo Henrique Batista [UNESP]; Risseti, Rafaela Mastrangelo [UNESP]; Ferreira, Karen Spadari; Gonoi, Tohru (FapUNIFESP (SciELO), 2015)
Nocardia is a ubiquitous microorganism related to pyogranulomatous infection, which is difficult to treat in humans and animals. The occurrence of the disease is on the rise in many countries due to an increase in immunosuppressive diseases and treatments. This report of cases from Brazil presents the genotypic characterization and the antimicrobial susceptibility pattern using the disk-diffusion method and inhibitory minimal concentration with E-test® strips. In summary, this report focuses on infections in young adult men, of which three cases were cutaneous, two pulmonary, one neurological and one systemic. The pulmonary, neurological and systemic cases were attributed to immunosuppressive diseases or treatments. Sequencing analysis of the 16S rRNA segments (1491 bp) identified four isolates of Nocardia farcinica, two isolates of Nocardia nova and one isolate of Nocardia asiatica. N. farcinica was involved in two cutaneous, one systemic and other pulmonary cases; N. nova was involved in one neurological and one pulmonary case; and Nocardia asiatica in one cutaneous case. The disk-diffusion antimicrobial susceptibility test showed that the most effective antimicrobials were amikacin (100%), amoxicillin/clavulanate (100%), cephalexin (100%) and ceftiofur (100%), while isolates had presented most resistance to gentamicin (43%), sulfamethoxazole/trimethoprim (43%) and ampicillin (29%). However, on the inhibitory minimal concentration test (MIC test), only one of the four isolates of Nocardia farcinica was resistant to sulfamethoxazole/trimethoprim.

Nocardia é um microorganismo ubiquitário relacionado a infecções piogranulomatosas, com difícil resolução tecidual em humanos e animais. A doença é mundialmente emergente devido ao aumento de doenças e tratamentos imunossupressores. Este relato de casos ocorridos no Brasil visa apresentar a identificação molecular dos isolados e o padrão de sensibilidade a antimicrobianos por disco-difusão e concentração inibitória mínima (CIM) através de fitas E-test®. Os casos ocorreram em homens, em idade adulta. Três quadros foram cutâneos, dois pulmonares, um neurológico e um sistêmico. O quadro respiratório, o neurológico e um sistêmico estavam associados à doença ou terapia imunossupressoras. O sequenciamento do gene 16S rRNA (1491pb) possibilitou a identificação de quatro isolados de Nocardia farcinica, dois de Nocardia nova e um de Nocardia asiatica. N. farcinica foi observada em dois casos dermatológicos, um pulmonar e um quadro sistêmico, N. nova foi isolada de um caso neurológico e outro pulmonar; e N. asiatica em um caso dermatológico. O teste de disco-difusão mostrou que amicacina (100%), amoxicilina/clavulanato (100%), cefalexina (100%) e ceftiofur (100%) foram mais efetivos; enquanto gentamicina (43%), sulfametoxazol/trimetoprim (43%) e ampicilina (29%) foram menos efetivos. No entanto, no teste de concentração inibitória mínima (CIM), apenas um dos quatro isolados da espécie Nocardia farcinica mostrou-se resistente a sulfametoxazole-trimetropina.
Identificação molecular e perfil de sensibilidade a antimicrobianos de sete isolados clínicos de Nocardia spp. no Brasil
Keywords: Nocardiosis; Nocardia; Opportunistic disease; Antimicrobial susceptibility test